Agro-MAPS (Mapping of Agricultural Production Systems) - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
The Agro-MAPS database has been created primarily to fill some critical gaps in the range of data needed for undertaking analyses related to land degradation, food security, farming systems studies, nutrient balances and climate change effects. The database currently contains data on crop production, area harvested and crop yields, for one or more years, for each country. The current web version of this database contains data for a subset of 20 crops that are considered to be of regional and global importance based on relative harvested areas. A tabular summary of the data contained in the Agro-MAPS database is available at http://www.fao.org/landandwater/agll/agromaps/agromapsdatasummary.pdf.; It is envisaged that other sub-national land-use information that are useful for characterizing agricultural production systems, will eventually be incorporated in Agro-MAPS. Detailed information on the Agro-MAPS initiative, including database preparation and future plans, are presented in a background paper at http://www.fao.org/landandwater/agll/agromaps/agromapsbackground.doc.; The Agro-MAPS database, which would eventually cover all regions of the world, is being prepared separately by FAO (for Africa and the Middle East), IFPRI (Latin America, Asia, Australia and New Zealand) and SAGE (the rest of the world).